Lithium-assisted proton conduction at 150 degrees C in a microporous triazine-phenol polymer - Nandi, Shyamapada; Dhavale, Vishal M.; Shalini, Sorout; Werner-Zwanziger, Ulrike; Singh, Harpreet; Kurungot, Sreekumar; Vaidhyanathan, Ramanathan (Advanced Materials Interfaces, 2015)
Keywords: conduction; hydrophobic polar frameworks; lithiated polymers; proton conduction; triazine-phenol polymers

Low band gap benzimidazole COF supported Ni3N as highly active OER catalyst - Nandi, Shyamapada; Singh, Santosh Kumar; Mullangi, Dinesh; Illathvalappil, Rajith; George, Leena; Vinod, Chathakudath P.; Kurungot, Sreekumar; Vaidhyanathan, Ramanathan (Advanced Energy Materials, 2016)
Covalent organic frameworks (COFs) have structures and morphologies closely resembling graphenes, whose modular construction permits atomiclevel manipulations. This, combined with their porous structure, makes them excellent catalyst supports. Here, the high electrocatalytic activity of a composite, formed by supporting Ni3N nanoparticles on a benzimidazole COF, for oxygen evolution reaction is shown. The composite oxidizes alkaline water with a near-record low overpotential of 230 mV @ 10 mA cm(-2) (eta(10)). This high activity is attributed to the ability of the COF to confine the Ni3N nanoparticles to size regimes otherwise difficult to obtain and to its low band gap character (1.49 eV) arising from the synergy between the conducting Ni3N nanoparticles and the pi-conjugated COF. The COF itself, as a metalfree self-standing framework, has an oxygen evolution reaction activity with 10 of 400 mV. The periodic structure of the COF makes it serve as a matrix to disperse the catalytically active Ni3N nanoparticles favoring their high accessibility and thereby good charge-transport within the composite. This is evident from the amount of O-2 evolved (230 mmol h(-1) g(-1)), which, to the best of our knowledge, is the highest reported. The work reveals the emergence of COF as supports for electrocatalysts.

Low-overpotential electrocatalytic water splitting with noble-metal-free nanoparticles supported in a sp(3) n-rich flexible COF - Mullangi, Dinesh; Dhavale, Vishal M.; Shalini, Sorout; Nandi, Shyamapada; Collins, Sean; Woo, Tom; Kurungot, Sreekumar; Vaidhyanathan, Ramanathan (Advanced Energy Materials, 2016)
Covalent organic frameworks (COFs) are crystalline organic polymers with tunable structures. Here, a COF is prepared using building units with highly flexible tetrahedral sp(3) nitrogens. This flexibility gives rise to structural changes which generate mesopores capable of confining very small (<2 nm sized) non-noble-metal-based nanoparticles (NPs). This nanocomposite shows exceptional activity toward the oxygen-evolution reaction from alkaline water with an overpotential of 258 mV at a current density of 10 mA cm(-2). The overpotential observed in the COF-nanoparticle system is the best in class, and is close to the current record of approximate to 200 mV for any noble-metalfree electrocatalytic water splitting system-the Fe-Co-Ni metal-oxide-film system. Also, it possesses outstanding kinetics (Tafel slope of 38.9 mV dec(-1)) for the reaction. The COF is able to stabilize such small-sized NP in the absence of any capping agent because of the COF-Ni(OH)(2) interactions arising from the N-rich backbone of the COF. Density-functional-theory modeling of the interaction between the hexagonal Ni(OH)(2) nanosheets and the COF shows that in the most favorable configuration the Ni(OH)(2) nanosheets are sandwiched between the sp(3) nitrogens of the adjacent COF layers and this can be crucial to maximizing their synergistic interactions.